Another Model of Communication's Possible Critical Experiences vs. the Market Tyranny - de la Piscina, Txema Ramirez (Javnost-The Public, 2006)
Along the lines of the alter-globalisation hope that has sprung forth in the social forums of Porto Alegre and Mumbai among others, the present article analyzes the underlying communicative experiences in four phenomena or specific situations: the Zapatista movement, the social reaction after the March 11 terrorist attacks in Madrid (2004), the incidents in Venezuela in 2002, and the proliferation of alternative sites on the internet. The author tries to demonstrate that in today’s society Another Model of Communication (AMC) is possible and that it may also be effective in its objectives. It is a model that radically questions the functions of each and every one of the elements that are part of the communication process as we know it today. The article maintains that taking control of the media is not necessary in order to implement this model. It even states that it would not be desirable for this to happen.